2017
DOI: 10.1088/1748-0221/12/12/c12056
|View full text |Cite
|
Sign up to set email alerts
|

Innovative thin silicon detectors for monitoring of therapeutic proton beams: preliminary beam tests

Abstract: To fully exploit the physics potentials of particle therapy in delivering dose with high accuracy and selectivity, charged particle therapy needs further improvement. To this scope, a multidisciplinary project (MoVeIT) of the Italian National Institute for Nuclear Physics (INFN) aims at translating research in charged particle therapy into clinical outcome. New models in the treatment planning system are being developed and validated, using dedicated devices for beam characterization and monitoring in radiobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…A new generation of silicon detectors based on UFSD technology and able to count single particles of therapeutic beams, and to measure the beam energy with time‐of‐flight techniques is under development by the medical physics group of the Turin division of the National Institute of Nuclear Physics (INFN) …”
Section: Detectors For Beam Monitoringmentioning
confidence: 99%
“…A new generation of silicon detectors based on UFSD technology and able to count single particles of therapeutic beams, and to measure the beam energy with time‐of‐flight techniques is under development by the medical physics group of the Turin division of the National Institute of Nuclear Physics (INFN) …”
Section: Detectors For Beam Monitoringmentioning
confidence: 99%
“…For bunch detection, secondary particle detectors can be used [20,41], whereas scintillator-based hodoscopes are generally proposed for single particle counting, with timing resolutions of several hundred picoseconds [39,42]. Thin ultra-fast silicon detectors (UFSD) have been explored for such purpose [43]. Using another technology, we have shown that a temporal resolution close to 100 ps rms is expected by means of diamond detectors, on condition that large areas are available with detector-grade crystals [24,44].…”
Section: Need For a Beam Tagging Systemmentioning
confidence: 99%
“…LGAD is a recent technology in silicon systems featuring detection of particles in a wide energy range with improved accuracy for timing and tracking measurements [20]. The LGAD application in particle therapy has been also recently investigated [21]. In the proposed setup, the TEPC will provide the energy deposition ϵ directly in a tissue-equivalent medium while the LGADs will offer information about particle spatial distribution with a precision of about 200 or 300 μm, depending on the chosen configuration.…”
Section: Introductionmentioning
confidence: 99%